2018
DOI: 10.2967/jnumed.118.219105
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Targeting in Thyroid Orthotopic Tumors Opens New Ways to Characterize Thyroid Cancer

Abstract: Preoperative characterization of thyroid nodules is challenging since thyroid scintigraphy fails to distinguish between benign and malignant lesions. Galectin-3 (gal-3) is expressed in well-differentiated and in undifferentiated thyroid cancer types but not in normal thyrocytes and benign thyroid lesions. Herein, we aimed to validate gal-3 targeting as a specific method to detect non-radioiodine-avid thyroid cancer in thyroid orthotopic tumor models. Methods: Papillary (BcPAP) and anaplastic (CAL62 and FRO82-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…The released Galectin-3 can bind to components of extracellular matrix and its membrane counterparts of other cells, which have in a wide range of biological events including cellular homeostasis, immune function, angiogenesis, tumor invasion and metastasis 25 . Galectin-3 has been reported as a diagnostic or prognostic marker linked to metastasis in many types of cancer such as thyroid 26,27 , breast cancer 28 , melanoma 29 , lung cancer 30 , sarcoma 31 , gastric cancer 32 , prostate cancer 33 and oral tongue cancer 34 . Here, we showed that Galectin-3 was greatly expressed in highly metastatic NPC cells compared to lowly metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The released Galectin-3 can bind to components of extracellular matrix and its membrane counterparts of other cells, which have in a wide range of biological events including cellular homeostasis, immune function, angiogenesis, tumor invasion and metastasis 25 . Galectin-3 has been reported as a diagnostic or prognostic marker linked to metastasis in many types of cancer such as thyroid 26,27 , breast cancer 28 , melanoma 29 , lung cancer 30 , sarcoma 31 , gastric cancer 32 , prostate cancer 33 and oral tongue cancer 34 . Here, we showed that Galectin-3 was greatly expressed in highly metastatic NPC cells compared to lowly metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Consecutive 4-μm-thick tumor sections of formalin-fixed/paraffin-embedded xenografts were stained for Hematoxylin & Eosin (H&E), Lipofuscin detection or macrophage infiltration, as reported [ 25 ] and detailed in Supplementary notes .…”
Section: Methodsmentioning
confidence: 99%
“…The conjugation with the AlexaFluor488 fluorescent dye and with a Cy5.5-NHS ester derivative, as well as the conjugation to desferrioxamine (DFO) and radiolabeling with 89 Z was carried out as previously reported ( supplementary material ) 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Tracer biodistribution and organ accumulation analyses were evaluated as previously described 20 . Whole length aortas (from the sinotubular junction to the iliac bifurcation) were excised under a dissection microscope (Zeiss Stemi DV4 SPOT) as described earlier 23 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation